Data set on the effectiveness of flip teaching on engineering students' performance in the physics lab compared to Traditional Methodology - Gómez-Tejedor, José A. (Data Brief, 2019)
This paper shows the data of the Flip Teaching and Traditional Methodology on the laboratory practice in two subjects, Physics and Electricity, of a technical degree. The laboratory and final grades of these subjects were shown in four consecutive years. The characteristics of all four years were quite similar, except that the Traditional teaching Methodology (TM) was used in two, while Flip Teaching methodology (FT) was applied in the other two. For further discussion, please refer to the scientific article entitled “Effectiveness of flip teaching on engineering students' performance in the physics lab” [1]. Additional segmentation data in three levels are presented in this data in brief paper.